2021
DOI: 10.3390/antiox10060821
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Its Consequences in the Blood of Rats Irradiated with UV: Protective Effect of Cannabidiol

Abstract: UVA/UVB radiation disturbs the redox balance of skin cells, and metabolic consequences can be transferred into the blood and internal tissues, especially after chronic skin exposure to UV radiation. Therefore, the aim of this study was to evaluate the effect of cannabidiol (CBD), an antioxidant and anti-inflammatory phytocannabinoid, on oxidative stress and its consequences in the blood of nude rats whose skin was exposed to UVA/UVB radiation for 4 weeks. It was shown that CBD penetrated the blood and in UVB-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 104 publications
1
15
1
Order By: Relevance
“…The antioxidant activity of CBD results mainly from the reduction of the excessive generation of oxidants, which promotes, among other, the inhibition of ROS-dependent lipid peroxidation [ 8 , 11 , 15 ]. As a consequence, the level of highly reactive products of polyunsaturated fatty acids oxidative fragmentation such as malondialdehyde (MDA) and 4-hydroxy-2-nonenal (4-HNE) as well as the level of their adducts with protein is reduced [ [16] , [17] , [18] ]. Moreover, recent studies indicate that CBD supports the maintenance of proteostasis under oxidative conditions by regulating molecular signalling in the biosynthesis and degradation of proteins under different conditions, in vivo and in vitro [ 17 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant activity of CBD results mainly from the reduction of the excessive generation of oxidants, which promotes, among other, the inhibition of ROS-dependent lipid peroxidation [ 8 , 11 , 15 ]. As a consequence, the level of highly reactive products of polyunsaturated fatty acids oxidative fragmentation such as malondialdehyde (MDA) and 4-hydroxy-2-nonenal (4-HNE) as well as the level of their adducts with protein is reduced [ [16] , [17] , [18] ]. Moreover, recent studies indicate that CBD supports the maintenance of proteostasis under oxidative conditions by regulating molecular signalling in the biosynthesis and degradation of proteins under different conditions, in vivo and in vitro [ 17 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was previously shown [ 20 ] that UVA/UVB irradiation of rats enhances the systemic production of ROS and lowers the antioxidant defense, which is conducive to the formation of oxidative stress. A similar situation is observed at the liver level of rats ( Figure 2 and Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…One natural compound with antioxidant and anti-inflammatory properties that has been highly researched recently is cannabidiol (CBD)—non-psychoactive phytocannabinoid [ 19 ]. In previous studies we showed that CBD after topical application penetrates into the bloodstream and is present in the blood plasma [ 20 ]. As a consequence, it is relatively quickly distributed to all organs with a good blood supply, such as the brain, heart, lungs and liver [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, described self-induced CBD applications can affect in an indefinite way not only on cell metabolism but also the entire human body. The experiments on mouse and rat models showed that topically applied CBD penetrates in to the blood and is transported throughout the bloodstream 27 , 44 . Additionally, it has been shown in another animal experiment that spot application of CBD shows even greater effects comparing to its systemic distribution 45 .…”
Section: Discussionmentioning
confidence: 99%
“…According to the such a broad spectrum of CBD action, connected with its properties of penetration through biological membranes and poly-layer cells cultures 21 , 22 , as well as its possibility of infiltration from the skin into the blood 27 , it is suggested that CBD may have significant impact on the oxidative, as well as pro-inflammatory changes induces by UV radiation. Therefore, the aim of this study was to analyze the changes in the proteomic profile of plasma from chronically UVA or UVB irradiated rats and define the effect on these changes of skin topically applied CBD.…”
Section: Introductionmentioning
confidence: 99%